Abdominal visceral and subcutaneous adipose tissue and associations with cardiometabolic risk in Inuit, Africans and Europeans: a cross-sectional study. Issue 9 (14th September 2020) - Rønn, Pernille Falberg; Andersen, Gregers Stig; Lauritzen, Torsten; Christensen, Dirk Lund; Aadahl, Mette; Carstensen, Bendix; Grarup, Niels; Jørgensen, Marit Eika
Abstract : Objectives: Abdominal fat has been identified as a risk marker of cardiometabolic disease independent of overall adiposity. However, it is not clear whether there are ethnic disparities in this risk. We investigated the associations of visceral adipose tissue (VAT) and abdominal subcutaneous adipose tissue (SAT) with cardiometabolic risk factors in three ethnic diverse populations of Inuit, Africans and Europeans. Design: Cross-sectional pooled study. Setting: Greenland, Kenya and Denmark. Methods: A total of 5113 participants (2933 Inuit, 1397 Africans and 783 Europeans) from three studies in Greenland, Kenya and Denmark were included. Measurements included abdominal fat distribution assessed by ultrasound, oral glucose tolerance test, hepatic insulin resistance, blood pressure and lipids. The associations were analysed using multiple linear regressions. Results: Across ethnic group and gender, an increase in VAT of 1 SD was associated with higher levels of hepatic insulin resistance (ranging from 14% to 28%), triglycerides (8% to 16%) and lower high-density lipoprotein cholesterol (HDL-C, −1.0 to −0.05 mmol/L) independent of body mass index. VAT showed positive associations with most of the other cardiometabolic risk factors in Inuit and Europeans, but not in Africans. In contrast, SAT was mainly associated with the outcomes in Inuit and Africans. Of notice was that higher SAT was associated with higher HDL-C in African men (0.11 mmol/L, 95% CI: 0.03 to 0.18) and with lower HDL-C in Inuit (−0.07 mmol/L, 95% CI: -0.12 to –0.02), but not in European men (−0.02 mmol/L, 95% CI: −0.09 to 0.05). Generally weaker associations were observed for women. Furthermore, the absolute levels of several of the cardiometabolic outcomes differed between the ethnic groups. Conclusions: VAT and SAT were associated with several of the cardiometabolic risk factors beyond overall adiposity. Some of these associations were specific to ethnicity, suggesting that ethnicity plays a role in the pathway from abdominal fat to selected cardiometabolic risk factors.